Optimization approaches for integrating cutting stock and flow shop scheduling with setup times in automotive chassis manufacturing - Souza, Raínne Florisbelo Gonçalves de (2025)
With the growing competitiveness in the market, industries are seeking ways to differentiate themselves and reduce production costs to increase profits. This has led many researchers to focus on studying integrated problems, as various aspects within an industrial setting are interconnected and can impact the overall production costs. This research specifically studies an integrated problem of cutting stock and permutation flow shop scheduling with sequence-dependent setup times found in the automotive industry as it is an unexplored area. The cutting stock process is responsible for providing the items required in production. Only when items are available, the flow shop production can be initiated. Besides that, there are sequence-dependent setup times between jobs to be processed on machines. Studying the integrated problem may improve the efficiency of the whole process. This thesis provides an understanding of the problem and its relevance in practical scenarios. A mixed integer linear programming is proposed as well as exact and heuristic resolution methods. For computational experiments, some instances were generated and the proposed methods were compared with one another. Results showed that the proposed exact method yielded quality solutions for small instances and the usage of a method to provide a good feasible initial solution may enhance the results. Furthermore, the proposed heuristic method based on the Adaptive Large Neighborhood Search (ALNS) algorithm outperformed the other tested methods, validating its quality and efficiency